A porous carbon carbon nanotube composite material and a preparation method and application thereof
Patent Information
- Application Number
- CN202611478395.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]为解决现有技术中多孔碳材料导电性差、比表面积易衰减、界面结合弱、整体抗变形能力较弱及工艺兼容性不足等技术问题,本发明提供了一种多孔碳碳纳米管复合材料及其制备方法与应用
[0036](1)本发明预掺杂路线将活化造孔、过渡金属热解还原与催化石墨化集于同一高温步骤,无需外加氢气,流程简化、能耗降低;后掺杂路线则支持分步操作,适配不同前驱体与生产条件,两条路线可灵活选用。
Smart Images

Figure CN123017755A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of novel energy storage carbon materials technology, specifically relating to a porous carbon nanotube composite material, its preparation method, and its application. Background Technology
[0002] Supercapacitors possess significant advantages such as high power density (up to 10 kW / kg), long cycle life (>500,000 cycles), and fast charge / discharge rates, making them a research hotspot in the field of electrochemical energy storage. However, their energy density (only 5~10 Wh / kg) has long been limited by the conductivity and specific surface area of the electrode materials themselves. Currently, high specific surface area activated carbon is commonly used as the active material in supercapacitor electrodes. However, the intrinsic amorphous carbon structure of this type of porous carbon results in extremely low conductivity. To reduce the internal resistance of the electrode, a large amount of inactive conductive agents (such as carbon black) often needs to be added, which not only occupies the mass and volume of the electrode but also severely restricts the improvement of the overall energy density of the device. Meanwhile, in the field of silicon-carbon anodes for lithium-ion batteries, although porous carbon is widely used as a carrier for high-capacity silicon-based materials, its low intrinsic conductivity makes it difficult to meet the electron transport requirements under high-rate charge and discharge conditions. At the same time, its pure porous framework structure has limited strength and cannot effectively buffer the volume expansion of silicon-based materials during lithium intercalation, which can easily lead to the collapse of the composite material structure and rapid capacity decay.
[0003] To improve the conductivity and structural stability of porous carbon-based materials, existing technologies have attempted to introduce carbon nanotubes (CNTs) to construct three-dimensional conductive networks, resulting in a variety of representative composite technologies. For example, patent CN109786128B discloses an electrostatic self-assembly strategy that combines modified carbon nanotubes with opposite charges with porous carbon to reduce the material's internal resistance. Patent CN116283363B utilizes plasma-enhanced chemical vapor deposition (PECVD) to grow carbon nanotubes in situ on the surface of a graphite matrix and achieves stable connections through carbon-carbon covalent bonds to improve conductivity and load high-capacity enhancers. Furthermore, patent CN114447304B uses hard carbon or porous carbon as a framework, combines in-situ growth of carbon nanotubes with vapor deposition, and deposits silicon to attempt to prepare lithium-ion battery anode materials. The above methods have improved the conductivity and interfacial bonding of porous carbon matrices to some extent. However, existing technologies still face many core defects: First, conductivity and pore formation are difficult to coordinate effectively. Conventional activation pore formation, while increasing specific surface area, will severely damage the carbon skeleton graphite microcrystalline structure, leading to a sharp drop in intrinsic conductivity. If pore preservation treatment is lacking after CVD growth of CNTs, micropore collapse and specific surface area loss are very likely to occur. Second, the existing composite process is relatively complex, often relying on external catalysts, complex solvent soaking or hydrogen reduction pretreatment, and it is difficult to balance process simplicity and industrialization cost. Third, the material function is relatively singular. Currently, most are designed only for the specific scenario of lithium-ion battery anodes, failing to systematically consider the extremely low internal resistance required when used as a supercapacitor electrode, and the high stress buffering capacity required when used as a silicon-carbon carrier, thus restricting its versatility and application potential in different high-power energy storage devices.
[0004] Therefore, developing a method for preparing porous carbon / carbon nanotube composite materials that can simultaneously achieve high specific surface area, high powder electrical conductivity, high deformation resistance, and strong process compatibility has significant industrial value and is an urgent technological need. Summary of the Invention
[0005] To address the technical problems of poor conductivity, easy decay of specific surface area, weak interfacial bonding, weak overall deformation resistance, and insufficient process compatibility of porous carbon materials in existing technologies, this invention provides a porous carbon nanotube composite material, its preparation method, and its application. This invention integrates and synergistically optimizes the processes of activated pore formation, transition metal-catalyzed graphitization, and in-situ CVD growth of carbon nanotubes, and introduces a second activation step, successfully preparing a porous carbon nanotube composite material with high specific surface area, high graphitization degree, excellent conductivity, and deformation resistance.
[0006] To achieve the above objectives, the technical solution of the present invention is as follows:
[0007] In a first aspect, the present invention provides a method for preparing porous carbon nanotube composite materials, including two optional schemes: a pre-doping route and a post-doping route.
[0008] The pre-doping route includes the following steps:
[0009] (1) Pre-doping mixing: The carbon-based precursor is uniformly mixed with the activator and the transition metal source in a certain proportion and then dried to obtain the mixed precursor;
[0010] (2) High-temperature synergistic activation: Under the protection of an inert atmosphere, the high-temperature activation treatment is carried out at 700-1000℃ for 1-5 h, simultaneously completing three functions: etching and creating pores on the carbon matrix by the activator, pyrolysis and reduction of the transition metal source into metal elemental nanoparticles, and catalytic rearrangement of amorphous carbon by metal elemental nanoparticles to generate graphite microcrystals.
[0011] (3) In-situ CVD growth of carbon nanotubes: The metal nanoparticles generated in-situ in step (2) are retained as catalysts. Carbon source gas is introduced at 650-1100℃ in an inert atmosphere to carry out chemical vapor deposition reaction, and carbon nanotubes are grown in-situ in the porous carbon framework to form an interpenetrating anchoring structure.
[0012] (4) Second stage activation: Stop the introduction of carbon source gas, switch to an inert atmosphere, and carry out the second stage physical activation and / or chemical activation treatment at 700-950℃ for 20-120 min;
[0013] (5) Post-processing purification: after acid washing, water washing until neutral, and drying, porous carbon nanotube composite material is obtained.
[0014] The post-doping route includes the following steps:
[0015] (1) Activation and pore formation: The carbon-based precursor is mixed with the activator and activated at high temperature of 700-1000℃ for 1-5 hours under an inert atmosphere to obtain a porous carbon matrix;
[0016] (2) Metal source loading: The activated porous carbon matrix is mixed with a transition metal source so that the transition metal source is uniformly loaded on the surface and pores of the porous carbon matrix. Then, it is subjected to high-temperature reduction treatment at 700-1000℃ for 0.5-2h under an inert atmosphere to obtain a porous carbon matrix loaded with metal elemental nanoparticles.
[0017] (3) In-situ CVD growth of carbon nanotubes: Using the metal nanoparticles loaded in step (2) as catalysts, carbon source gas is introduced at 650-1100℃ under an inert atmosphere to carry out chemical vapor deposition reaction, and carbon nanotubes are grown in-situ in the porous carbon framework.
[0018] (4) Second stage activation: Stop the introduction of carbon source gas, switch to an inert atmosphere, and carry out the second stage physical activation and / or chemical activation treatment at 700-950℃ for 20-180 min;
[0019] (5) Post-processing purification: after acid washing, water washing until neutral, and drying, porous carbon nanotube composite material is obtained.
[0020] Preferably, in the pre-doping route step (1), the mass ratio of activator to carbon-based precursor is 1:1 to 4:1, preferably 1.5:1 to 3:1; the amount of transition metal source added is 0.5% to 15% of the mass of metal element to the mass of carbon-based precursor, preferably 1% to 10%; the drying temperature is 60 to 120°C, and the drying time is 6 to 24 hours.
[0021] Preferably, the carbon-based precursor is selected from any one or more of biomass, coal tar pitch, petroleum pitch, petroleum coke, resin, etc.; the activator is selected from any one or more of KOH, NaOH, K2CO3, ZnCl2, H3PO4, or from any one or more of CO2 and water vapor; the metal element in the transition metal source is selected from any one or more of Fe, Ni, Co, Cu, Mo, Mn.
[0022] Preferably, when the transition metal source is a soluble salt, it is pre-dissolved in water to form an aqueous solution, and then mixed and impregnated with a carbon-based precursor and an activator; when the transition metal source is an insoluble solid powder, it is uniformly mixed with a carbon-based precursor and an activator by solid-phase grinding.
[0023] Preferably, in the high-temperature synergistic activation step, the heating rate is 3-10℃ / min, the activation temperature is 750-950℃, and the activation time is 2-4 h.
[0024] Preferably, in the in-situ CVD growth of carbon nanotubes step, the carbon source gas is selected from any one or more of methane, ethylene, acetylene, ethanol, and toluene, preferably one or more of methane, ethylene, and acetylene; the carbon source gas flow rate is 10–200 sccm; the reaction time is 20–240 min, preferably 30–90 min; and the CVD growth temperature is 680–950℃.
[0025] Preferably, in the second activation step, the physical activation medium is selected from any one or more of water vapor and CO2, and the chemical activator is selected from any one or more of KOH, NaOH, and K2CO3; the activation temperature is 750-900℃, and the activation time is 30-120 min.
[0026] Preferably, in the post-processing purification step, acid washing uses an aqueous solution of 0.5–3 mol / L inorganic acid for 1–6 h; drying temperature is 100–120 °C for 6–24 h.
[0027] Secondly, the present invention provides a porous carbon nanotube composite material prepared by the above-described method. The porous carbon nanotube composite material is composed of the following three structural units:
[0028] (1) Porous carbon matrix: It has abundant micropores and / or mesopores, with a specific surface area of 600 to 3500 m². 2 / g, pore volume 0.5–3.5 cm³ 3 / g;
[0029] (2) Graphite crystals: uniformly distributed inside the porous carbon matrix, formed by transition metal catalysis of amorphous carbon graphitization, with a crystallite size of 1 to 20 nm and a Raman ID / IG value of 0.6 to 1.0;
[0030] (3) Carbon nanotubes: inserted and anchored in the framework of the porous carbon matrix, with a diameter of 2 to 50 nm and a length of 50 nm to 50 μm, and are of a few layers or multiple layers.
[0031] The graphite microcrystals and carbon nanotubes synergistically construct a three-dimensional interconnected conductive network within and on the surface of the porous carbon matrix. The carbon nanotubes are grown in situ within the porous carbon framework using transition metal elemental catalysts, exhibiting an in-situ chemical / metallurgical interface with the porous carbon matrix, rather than being physically mixed.
[0032] Thirdly, the present invention provides the application of the above-mentioned porous carbon nanotube composite material in supercapacitors or silicon-carbon anodes of lithium-ion batteries.
[0033] Preferably, in the supercapacitor, the composite material serves as the electrode active material, exhibiting a specific capacitance of 150–200 F / g in an organic electrolyte system, a high-rate capacity retention of ≥90% at 10 A / g, and an equivalent series internal resistance ≤2.5 mΩ.
[0034] Preferably, in the silicon-carbon anode of a lithium-ion battery, the composite material serves as a nano-silicon carrier, and the resulting silicon-carbon anode has a reversible capacity ≥1800 mAh / g, a high-rate capacity retention rate of 10 A / g ≥45%, and a capacity retention rate of ≥80% after 1000 cycles.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] (1) The pre-doping route of the present invention integrates activation pore formation, transition metal pyrolysis reduction and catalytic graphitization into the same high-temperature step, without the need for external hydrogen, simplifying the process and reducing energy consumption; the post-doping route supports step-by-step operation, adapts to different precursors and production conditions, and the two routes can be flexibly selected.
[0037] (2) The present invention enables carbon nanotubes and porous carbon skeleton to form a chemical / metallurgical interface through in-situ growth, which is uniformly distributed and firmly bonded, avoiding the problems of easy agglomeration and easy detachment of physical mixing, and constructing a stable three-dimensional conductive pathway.
[0038] (3) The present invention introduces a second activation step to repair the pore blockage caused by carbon deposition after CVD growth. While retaining the conductivity enhancement effect of carbon nanotubes, it restores the high specific surface area of porous carbon, thus solving the technical problem that the specific surface area inevitably decreases due to CVD growth.
[0039] (4) In this invention, graphite microcrystals enhance intrinsic electrical conductivity, and carbon nanotubes construct long-range electrical conductivity and mechanical support, with a specific surface area of 600–3500 m². 2 / g, internal resistance ≤1.9 mΩ, supercapacitor specific capacity ≥188 F / g, rate retention ≥95%; when used as a silicon-carbon anode, the high specific surface area for silicon storage, conductive grid and confined buffer work together to achieve a reversible capacity ≥2029 mAh / g and a rate retention ≥88% after 1000 cycles. It is also suitable for various precursors such as biomass, asphalt, and resin, and has broad prospects for industrialization. Attached Figure Description
[0040] Figure 1 This is a process flow diagram for the preparation of the porous carbon nanotube composite material of the present invention, including the pre-doping route and the post-doping route.
[0041] Figure 2 The images show scanning electron microscope (SEM) images of the porous carbon prepared in Comparative Example 1 and the porous carbon / carbon nanotube composite prepared in Example 1 of this invention.
[0042] Figure 3 The image shows a transmission electron microscope (TEM) image of the porous carbon nanotube composite obtained in Example 1 of this invention; the left image shows that the diameter of the carbon nanotubes in the porous carbon nanotube composite is in the range of 30-40 nm (the specific thickness and length are related to the metal type and CVD deposition process); the middle image is a local magnification of the carbon nanotube portion of the composite, showing multiple graphene layers (interlayer spacing d). 002 The concentric tubes (0.340 nm) are typical multi-walled carbon nanostructures; the TEM image on the right is a local magnification of the porous carbon in the composite, showing a large number of interlayer spacing d distributed within the porous carbon. 002 =0.351nm, La crystal plane length 5-10nm graphite microcrystals (the specific interlayer spacing and microcrystal size are related to the raw materials and production process).
[0043] Figure 4 This is a local magnified comparison of the (002) diffraction peak in the X-ray diffraction (XRD) patterns of the samples of Example 1, Comparative Example 1 and Comparative Example 5 of the present invention (the vertical axis is twice the Bragg diffraction angle, 2θ). Detailed Implementation
[0044] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the scope of protection of this invention.
[0045] After reading the contents disclosed in this invention, those skilled in the art can make appropriate adjustments or substitutions to the process parameters of the methods and applications described in this invention without departing from the spirit and scope of this invention. Such obvious adjustments, substitutions or combinations should be included within the protection scope of this invention.
[0046] Unless otherwise specified, the materials, reagents, instruments and testing methods used in the following embodiments can be obtained commercially or prepared, operated and implemented with reference to conventional methods disclosed in the art.
[0047] It should be noted that the "carbon-based precursor" mentioned in this invention refers to any carbon-containing substance that can be carbonized at high temperatures to form carbon materials, including but not limited to one or more of the following: biomass raw materials (such as coconut shells, walnut shells, apricot shells, bamboo, wood chips, etc.), polymers (such as phenolic resins, polyacrylonitrile, polyvinylidene fluoride, etc.), coal, asphalt, petroleum coke, and commercially available base carbon materials (such as activated carbon, carbon black, graphene, etc.). The technical solution of this invention has broad applicability to carbon-based precursors.
[0048] The "activator" described in this invention is a chemical activator and / or a physical activation medium. The chemical activator is selected from any one or more of potassium hydroxide (KOH), potassium carbonate (K₂CO₃), sodium hydroxide (NaOH), and sodium carbonate (Na₂CO₃); the physical activation medium is selected from any one or two of water vapor (H₂O) and carbon dioxide (CO₂). Chemical activation and physical activation can be used alone or in combination, depending on the target pore structure requirements and cost considerations.
[0049] The "transition metal source" described in this invention is selected from any one or more of transition metal elemental powders, transition metal organic salts, and transition metal inorganic salts. The metal element is selected from one or more of iron (Fe), nickel (Ni), cobalt (Co), copper (Cu), and molybdenum (Mo). The transition metal source can be introduced in the form of an aqueous solution (such as an aqueous solution of nitrates, chlorides, or acetates) or directly incorporated in the form of a solid powder (such as elemental metal powder or solid metal salt powder), without the need for organic solvents (such as N-methylpyrrolidone, carbon tetrachloride, etc.). This feature makes the process of this invention environmentally friendly and economical, while also broadening the range of raw material selection.
[0050] Example 1: A porous carbon nanotube composite material
[0051] This embodiment adopts Figure 1 The pre-doping process route in this study uses biomass (coconut shell) as a carbon-based precursor, KOH as an activator, and ferric nitrate as a transition metal source. The specific steps are as follows:
[0052] (1) Raw material pretreatment: Coconut shell biomass is used as a carbon-based precursor. After being crushed and ground, it is passed through a 100-mesh sieve (sieve aperture size 150 μm) and dried at 80℃ for 12 h for later use. The main components of coconut shell biomass are cellulose, hemicellulose and lignin. After high-temperature carbonization, it can form carbon materials with rich pore structure.
[0053] (2) Pre-doping and mixing: Take 1 g of the above biomass powder and mix it with KOH at a mass ratio of 1:3 (i.e., the amount of KOH used is 3 g), add 3 mL of 0.5 mol / L ferric nitrate (Fe(NO3)3·9H2O) aqueous solution, stir evenly, soak at room temperature for 2 h, and dry at 80℃ for 12 h to obtain the mixed precursor.
[0054] (3) High temperature synergistic activation: The mixed precursor was placed in a tube furnace and heated to 800°C at 5°C / min under nitrogen inert atmosphere protection (nitrogen flow rate 100 sccm). The temperature was kept constant for 2 h and then naturally cooled to room temperature to obtain the crude product of graphite microcrystal modified porous carbon.
[0055] In the above steps, while KOH etches the carbon matrix to create pores, ferric nitrate is pyrolyzed to generate Fe2O3 nanoparticles, which then react with carbon to be reduced to Fe elemental nanoparticles. The Fe elemental nanoparticles catalyze the rearrangement of amorphous carbon atoms to generate graphite microcrystals.
[0056] (4) In-situ growth of carbon nanotubes: Maintain an inert atmosphere in the tubular furnace (nitrogen flow rate 100 sccm), continue to heat to 850℃, and introduce additional methane carbon source gas (flow rate 50 sccm) for 40 min. Methane is cracked under the catalysis of Fe elemental nanoparticles, and carbon atoms are precipitated on the surface of metal particles to form carbon nanotubes, which are interwoven and anchored in the porous carbon framework.
[0057] (5) Second stage activation: Maintain the temperature at 850℃, stop the introduction of methane, switch to nitrogen atmosphere (flow rate 100 sccm), and introduce water vapor (flow rate 1 mL / min, liquid water enters the tube furnace after vaporization) for the second stage physical activation for 30 min, in order to restore and further construct the specific surface area and blockage of micropores that may be reduced due to carbon deposition.
[0058] (6) Post-treatment: The product was washed with 1 mol / L hydrochloric acid for 2 h to remove the metal catalyst particles and impurities exposed on the surface. Then it was repeatedly washed with deionized water until neutral (pH≈7) and dried at 100℃ for 12 h to obtain biomass-based porous carbon nanotube composite carbon material.
[0059] Example 2: A porous carbon nanotube composite material
[0060] This embodiment adopts Figure 1 The pre-doping process route in this study uses coal tar pitch as a carbon-based precursor, potassium carbonate and sodium hydroxide as activators, and nickel nitrate as a transition metal source. The specific steps are as follows:
[0061] (1) Raw material pretreatment: Asphalt was used as a carbon-based precursor, ground through a 100-mesh sieve, and dried at 80℃ for 6 h to remove moisture.
[0062] (2) Pre-doping and mixing: Take 1 g of asphalt powder and mix it with potassium carbonate (K2CO3) and sodium hydroxide (NaOH) composite activator at a mass ratio of 1:1.5:0.5 (i.e., 1.5 g of K2CO3 and 0.5 g of NaOH). Add 0.1 g of nickel nitrate (Ni(NO3)2·6H2O) solid powder and grind and mix it thoroughly in a mortar for 30 min to make the components evenly dispersed.
[0063] (3) Physical combined high-temperature activation: The mixed precursor was placed in a tube furnace and heated to 850℃ at 5℃ / min under nitrogen protection. Chemical activation was first performed for 1 h (K2CO3 and NaOH etching to create pores), and water vapor (flow rate 0.5 mL / min liquid water vaporization) was simultaneously introduced for physical combined activation. The total activation time was 2.5 h. In this step, nickel nitrate was pyrolyzed and reduced to Ni elemental nanoparticles, catalyzing the conversion of pitch carbon into graphite microcrystals.
[0064] (4) CVD growth of carbon nanotubes: Under nitrogen protection, the temperature is raised to 900℃, and acetylene (C2H2) carbon source gas (flow rate 30 sccm) is introduced. The reaction is carried out for 30 min, and carbon nanotubes are grown by catalysis using the in-situ generated Ni elemental nanoparticles.
[0065] (5) Second stage activation: Stop the acetylene flow, continue to maintain the nitrogen atmosphere, raise the temperature to 950℃, and introduce CO2 (flow rate 100 sccm) for the second stage physical activation for 30 min to restore the specific surface area.
[0066] (6) Post-treatment: The product was acid-washed with 1 mol / L hydrochloric acid, washed with deionized water until neutral, and dried at 100℃ for 12 h to obtain pitch-based porous carbon nanotube composite carbon material.
[0067] Example 3: A porous carbon nanotube composite material
[0068] This embodiment adopts Figure 1 The post-doping process route in this study involves using pre-carbonized resin carbon as a carbon-based precursor, CO2 as an activator, and cobalt nitrate as a transition metal source. A porous carbon nanotube composite material is constructed through a strategy of first activating and creating pores, followed by loading the metal. The specific steps are as follows:
[0069] (1) Physical activation to create pores: 2 g of pre-carbonized resin carbon was placed in a tube furnace and physically activated at 900 °C for 2 h using 150 sccm of CO2 as the activation medium to obtain a porous carbon matrix with abundant micropores / mesopores. This step utilizes the oxidative etching effect of CO2 on the carbon skeleton to form a pore network, providing loading sites for subsequent metal catalysts.
[0070] (2) Metal source loading: After the activated product was purified by acid washing to remove ash and surface impurities, it was placed in 15 mL of 0.15 mol / L cobalt nitrate (Co(NO3)2) aqueous solution and impregnated and stirred at room temperature for 3 h to allow Co to be loaded. 2+ Ions diffuse fully into the pores of the carbon matrix; then dry at 80°C to uniformly load the metal salt precursor onto the porous carbon surface and pore walls.
[0071] (3) High-temperature reduction: Under nitrogen atmosphere protection (flow rate 100 sccm), the temperature is increased to 800℃ at 5℃ / min and reduced at a constant temperature for 1 h. During this process, cobalt nitrate is pyrolyzed to generate cobalt oxide, which then reacts with carbon to generate catalytically active Co elemental nanoparticles in situ, which are uniformly anchored in the carbon channels.
[0072] (4) CVD growth: Maintain a nitrogen atmosphere, raise the temperature to 880℃, introduce methane carbon source gas at a flow rate of 60 sccm, and react for 45 min. Methane is cracked under the catalysis of Co nanoparticles, and carbon atoms are precipitated on the surface of metal particles and grow in a directional manner to form carbon nanotubes, which are intercalated and anchored in the porous carbon framework to construct a three-dimensional conductive network.
[0073] (5) Second stage activation: Stop the introduction of methane, keep the temperature constant at 880℃, switch to nitrogen atmosphere and introduce water vapor (liquid water at a flow rate of about 1 mL / min after vaporization) for the second stage of physical activation, which lasts for 30 min. This step uses water vapor to clear the micropores that may be blocked during carbon deposition, while restoring and further improving the specific surface area and porosity of the composite material.
[0074] (6) Post-treatment: The product was washed with 1 mol / L hydrochloric acid for 2 h to remove the metal catalyst residues exposed on the surface, and then washed repeatedly with deionized water until neutral (pH≈7), and dried at 100℃ for 12 h to obtain resin carbon-based porous carbon / carbon nanotube composite carbon material.
[0075] Example 4: A porous carbon nanotube composite material
[0076] This embodiment corresponds to Figure 1 The post-doping route in this study: using fruit shell biomass as a carbon-based precursor, CO2 as an activator, and ferric nitrate as a transition metal source, porous carbon nanotube composite materials were prepared by first activating and creating pores, and then loading the catalyst. The specific steps are as follows:
[0077] (1) Physical activation to create pores: Using fruit shell biomass as a carbon-based precursor, the material was crushed and ground and then passed through a 100-mesh sieve (sieve aperture size 150 μm). 2 g of the sieved powder was placed in a tube furnace and physically activated at 900℃ for 2.5 h using CO2 as the activation medium (flow rate 200 sccm). After cooling, the material was discharged to obtain a porous carbon matrix. The CO2 etching effect endowed the carbon skeleton with abundant micropores and mesopores, providing sufficient adhesion space for subsequent metal impregnation.
[0078] (2) Metal source loading: The above porous carbon matrix was placed in a 0.2 mol / L ferric nitrate (Fe(NO3)3) aqueous solution and impregnated and stirred at room temperature for 3 h to allow Fe to be loaded. 3+ Ions fully penetrate into the interior of carbon channels; then dry at 80°C to ensure that the metal salt is uniformly loaded on the surface and pore walls of the carbon matrix, thus ensuring a high degree of dispersion of the catalyst precursor.
[0079] (3) High-temperature reduction: Under nitrogen atmosphere protection (flow rate 100 sccm), the temperature is increased to 800℃ at 5℃ / min and held at a constant temperature for 1h. Ferric nitrate decomposes upon heating to generate iron oxide, which then undergoes a carbothermic reduction reaction with carbon to transform into Fe elemental nanocatalytic particles, which are firmly anchored in the pores of the carbon matrix.
[0080] (4) In-situ CVD growth of carbon nanotubes: Maintain a nitrogen atmosphere, continue heating to 850℃, introduce methane carbon source gas at a flow rate of 50 sccm, and react for 40 min. Methane is cracked under the catalysis of Fe nanoparticles, carbon atoms are precipitated on the metal surface and grow along a specific direction, forming carbon nanotubes in situ, which are uniformly dispersed in the porous carbon framework, enhancing the structural stability and conductivity of the composite material.
[0081] (5) Second stage activation: Stop the introduction of methane, maintain the temperature at 850℃, and introduce water vapor (liquid water at a flow rate of about 1 mL / min after vaporization) under a nitrogen atmosphere for the second stage of physical activation, which lasts for 30 min. This process effectively removes micropores that may be blocked by the growth of carbon nanotubes, restores the specific surface area, and further creates pores to optimize the pore size distribution.
[0082] (6) Post-treatment: The product was washed with 1 mol / L hydrochloric acid for 2 h to remove residual iron catalyst particles and soluble impurities. It was then washed repeatedly with deionized water until neutral (pH≈7) and dried at 100℃ for 12 h to obtain the fruit shell biomass-based porous carbon nanotube composite carbon material.
[0083] Comparative Example 1
[0084] This comparative example uses the same coconut shell biomass precursor and KOH activation conditions (800°C, 3h) as Example 1, but does not add any transition metal source and does not perform CVD growth of carbon nanotubes, only preparing pure activated porous carbon materials.
[0085] Comparative Example 2
[0086] This comparative example employs a physical mixing and doping process, aiming to compare it with the in-situ chemical vapor deposition carbon nanotube growth scheme of Example 1, in order to verify the advantages of in-situ growth over simple physical mixing in terms of carbon nanotube dispersion uniformity, interfacial bonding strength, and three-dimensional conductive network construction effect.
[0087] The specific steps are as follows:
[0088] (1) Substrate preparation: The metal-catalyzed graphitized porous carbon prepared in Comparative Example 1 was used as the carbon-based substrate material (this material is consistent with the product obtained in steps (1) to (3) of Example 1) as the source of porous carbon components.
[0089] (2) Proportioning and weighing: Take the above porous carbon powder and commercial multi-walled carbon nanotubes (diameter 10-20 nm, length 1-5 μm) and weigh them accurately at a mass ratio of 95:5.
[0090] (3) Ball milling physical mixing: The two weighed powders are placed in a planetary ball mill, and anhydrous ethanol is used as the wet dispersion medium. The ball-to-powder ratio is controlled at 10:1. The mixture is ball milled at 300 r / min for 2 h at room temperature, so that commercial carbon nanotubes are physically attached to the surface and pore edges of porous carbon through mechanical force.
[0091] (4) Post-drying treatment: Take out the ball-milled mixed slurry and dry it in an 80℃ constant temperature drying oven for 12 hours to finally obtain a physically mixed porous carbon / carbon nanotube composite control sample.
[0092] Comparative Example 3
[0093] This comparative example uses the exact same steps as Example 1, but omits the second activation step (i.e., directly cooling, acid washing, and drying after in-situ growth of carbon nanotubes).
[0094] Comparative Example 4
[0095] This comparative example refers to the process conditions disclosed in Example 1 of Chinese Invention Patent CN114447304B (publication date 2022.05.06) to prepare a hard carbon composite anode material. The purpose is to use the in-situ grown carbon nanotube / amorphous carbon double-coated hard carbon composite material under the patent scheme as a comparison sample with Example 1 of this invention (biomass-based porous carbon / in-situ CVD carbon nanotube composite) to verify the influence of the differences in the selection of carbon source precursor, activation pore-forming method and in-situ growth process of this invention on the final material structure and performance.
[0096] The specific steps are as follows:
[0097] (1) Weigh 100 g of phenolic resin (as a hard carbon precursor) and mix it with 500 mL of potassium hydroxide aqueous solution with a mass concentration of 5 wt%. Stir continuously for 5 h, and after centrifugation, dry under vacuum at 80 °C for 24 h. Place the dried mixture in a tube furnace and heat it to 800 °C at a heating rate of 5 °C / min under an argon protective atmosphere. Hold it at the same temperature for 3 h, and after naturally cooling to room temperature, grind and pulverize it to obtain a porous hard carbon precursor (porosity of about 20% and average pore size of about 20 nm).
[0098] (2) Dissolve 2 g of ferric chloride (FeCl3) in 100 mL of N-methylpyrrolidone (NMP) organic solvent to prepare a catalyst solution with a mass concentration of 2 wt%. Then add 10 g of pitch and stir until completely dissolved. Add 100 g of the porous hard carbon precursor powder obtained in step (1) to the mixed solution, stir continuously, and soak for 48 h to allow the catalyst and pitch to fully penetrate into the pores of the porous carbon. After soaking, filter and vacuum dry.
[0099] (3) The dried supported catalyst and the hard carbon precursor of pitch were transferred to a tube furnace, and methane (CH4) carbon source gas was introduced under an inert atmosphere. The mixture was carbonized at 800℃ for 3 h. During this process, the pitch cracked to generate amorphous carbon that coated the surface of the hard carbon. At the same time, the Fe catalyst catalyzed the cracking of methane to grow carbon nanotubes in situ, achieving a double coating of carbon nanotubes and amorphous carbon. After carbonization, the mixture was naturally cooled to room temperature, pulverized and sieved to obtain the hard carbon composite anode material.
[0100] Comparative Example 5
[0101] This comparative example uses the same biomass precursor, activator, and metal salt doping scheme as Example 1, but deliberately omits the in-situ chemical vapor deposition (CVD) growth of carbon nanotubes and the second-stage water vapor activation step, and only prepares metal-catalyzed graphitized porous carbon materials.
[0102] Example 1: Physical characterization test of composite materials
[0103] To evaluate the microstructure, graphitization degree, morphological characteristics, and electrical conductivity of the porous carbon nanotube composite material prepared in this invention and its comparative samples, and to verify the modification effect of in-situ grown carbon nanotubes on porous carbon substrates, systematic material characterization tests were conducted. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to observe the sample morphology; the specific surface area was determined by nitrogen adsorption-desorption method; and X-ray diffraction (XRD) was used to analyze the graphite microcrystalline structure. Figure 4 The electrical conductivity of the powder was tested using the four-probe method.
[0104] Morphological observation: SEM images ( Figure 2 The images show that pure activated porous carbon (Comparative Example 1) exhibits a loose granular morphology with relatively uniform pore distribution; while in the porous carbon nanotube composite of Example 1, a large number of carbon nanotubes are uniformly interspersed between the porous carbon framework, forming a three-dimensional conductive network with uniform diameter, good dispersion, and no obvious agglomeration. TEM images ( Figure 3Further evidence confirms that the carbon nanotubes have clear walls and a crystal interplanar spacing of approximately 0.340 nm, corresponding to the typical interlayer spacing of the (002) plane of graphite, indicating that the carbon nanotubes have a high degree of graphitization. At the same time, there are some graphitized microcrystalline regions at the edge of the porous carbon matrix, exhibiting a short-range ordered structure, which confirms the synergistic effect of metal-catalyzed graphitization.
[0105] Specific surface area analysis: The specific surface area of Example 1 is as high as 2600 m². 2 / g, significantly higher than that of Comparative Example 3 (1560 m) 2 / g) and Comparative Example 4 (14 m 2 Although CVD-grown carbon nanotubes may cause some micropore blockage, the specific surface area is effectively restored by subsequent second-stage water vapor activation, and new pores are further constructed, so that the composite material has both high specific surface area and well-developed pore structure, which is beneficial to ion transport and exposure of active sites.
[0106] Graphite microcrystalline structure (XRD): composed of Figure 4 The results show that the (002) peak of Example 1 is significantly shifted to a higher angle (compared to the broad peak of amorphous carbon in Comparative Example 1), indicating that the interlayer spacing of graphite is reduced and the degree of graphitization is significantly improved. Although Comparative Example 5 was catalyzed by metal but did not undergo CVD and the second stage activation, its (002) peak position is between that of Comparative Example 1 and Example 1, indicating that metal catalysis can induce partial graphitization, but without carbon nanotube growth and the second stage activation, the degree of graphitization and the integrity of the pore structure are not as good as those of Example 1.
[0107] Electrical conductivity: The powder conductivity of Example 1 reached 233.5 S / m, which is much higher than that of Comparative Example 1 (23.6 S / m), Comparative Example 4 (59.1 S / m), and Comparative Example 5 (75.2 S / m), and even better than that of Comparative Example 2 (159.1 S / m). This is attributed to the in-situ grown carbon nanotubes acting as highly efficient conductive bridges, connecting isolated porous carbon particles. At the same time, the graphitized microcrystals formed by metal catalysis also reduced the interfacial contact resistance, thereby significantly improving the electron transport capability of the composite material.
[0108] In summary, the porous carbon nanotube composite materials prepared by this invention through pre-doping or post-doping routes possess high specific surface area, high graphitization degree, and excellent electrical conductivity, demonstrating broad application prospects as high-performance electrode materials. Among these, the in-situ grown carbon nanotubes synergistically construct a three-dimensional conductive network with the porous carbon matrix, combined with subsequent activation processes to effectively repair and optimize the pore structure, is the key technology for achieving breakthroughs in the overall performance of the material.
[0109] Example 2: Application of composite materials in supercapacitors
[0110] To systematically evaluate the electrochemical performance of the porous carbon nanotube composite material prepared in this invention in organic supercapacitors, verify its practical potential as a high-performance electrode material, and explore the influence of different processing conditions on capacitive behavior, we assembled CR2032 coin-type supercapacitors using the materials prepared in Examples 1-4 and Comparative Examples 1-5 as active materials. Constant current charge-discharge tests and rate performance evaluations were conducted. The specific steps are as follows:
[0111] (1) Preparation of capacitor electrode: The active material, sodium carboxymethyl cellulose (CMC) binder, styrene-butadiene rubber (SBR) binder and conductive carbon black (Super P) were mixed in a mass ratio of 90:2:3:5. An appropriate amount of deionized water was added and stirred into a uniform slurry. The slurry was coated onto an aluminum foil current collector with a thickness of 20 μm using a doctor blade coating method. The coating thickness was about 150 μm. After vacuum drying at 100℃ for 12 h, the electrode was cut into circular electrodes with a diameter of 12 mm. The mass of the active material was accurately weighed and recorded.
[0112] (2) Assembly of button capacitor: In a glove box filled with argon (water and oxygen content <0.1 ppm), CR2032 type button supercapacitor is assembled in the following order: positive electrode shell, electrode, cellulose diaphragm (16 mm in diameter), 80 μL of 1 mol / L tetraethylammonium tetrafluoroborate (Et4NBF4) propylene carbonate (PC) electrolyte, electrode, gasket, spring, and negative electrode shell.
[0113] (3) Electrochemical testing: After the assembled capacitor was kept at 25℃ for 4 h, constant current charge-discharge tests were performed at current densities of 1 A / g, 2 A / g, 5 A / g, and 10 A / g within a voltage window of 1.35–2.7V. Specific capacitance (C, F / g) was calculated using the formula C = 2I·Δt / (m·ΔU) (where I is the discharge current, Δt is the discharge time, m is the mass of the active material of a single electrode, and ΔU is the discharge voltage range); rate performance was characterized by the capacity retention rate at 10 A / g (as a percentage of the initial capacity at 1 A / g). Equivalent series internal resistance was determined according to ESR = ΔV_IR. drop / (2I) calculation (where I is the discharge current, and ΔV_Irdrop is the static value after 5s of full charge). The electrochemical performance test results of each sample are summarized in Table 1.
[0114] Table 1 Comparison of supercapacitor performance of each sample
[0115]
[0116] As shown in Table 1, all embodiments of the present invention exhibit excellent comprehensive electrochemical performance (Specific capacity of Example 1: 188 F / g, Internal resistance: 1.9 mΩ, Retention rate: 95.2%; Examples 2 and 4: 175 F / g and 170 F / g, respectively, with retention rates of 93.5% and 91.6%; Example 3: 162 F / g, 90.8%), proving that the technical solution has wide applicability to different carbon precursors (biomass, pitch, resin carbon) and process routes (pre-doping and post-doping). The core of its performance advantage lies in the synergistic effect of "in-situ grown carbon nanotubes - porous carbon substrate - second-stage activation": the in-situ grown carbon nanotubes construct a three-dimensional conductive network in the carbon skeleton through strong interfacial bonding, which not only greatly reduces the internal resistance (only 1.9 mΩ in Example 1, while as high as 5.1 mΩ in Comparative Example 1), but also provides a continuous electron transport channel; at the same time, the high specific surface area of the porous carbon substrate provides sufficient sites for ion storage, while the second-stage water vapor activation precisely repairs the pore blockage caused by carbon deposition during the CVD process, ensuring that the ion transport path is unobstructed (the specific capacity of Comparative Example 3, which omits this step, drops sharply to 90 F / g and the retention rate is only 62.0%). It is this synergistic construction of the "conductive network—high specific surface area substrate—through-pore channels" that enables Example 1 to outperform Comparative Example 2 (170 F / g, 3.3 mΩ), which uses physically mixed commercial carbon nanotubes, and Comparative Example 5 (180 F / g, 3.6 mΩ, 87.0%), which only involves metal catalysis and graphitization but lacks CVD growth and a second-stage activation. It also significantly surpasses the prior art Comparative Example 4 (15 F / g, 6.8 mΩ, 41.3%). Furthermore, this synergistic effect can be achieved through both pre-doping and post-doping routes. In summary, this invention, through synergistic process design, successfully achieves a breakthrough in the comprehensive performance of porous carbon / carbon nanotube composite materials, demonstrating significant application advantages in organic supercapacitors.
[0117] Example 3: Application of composite materials in silicon-carbon anode carriers
[0118] To systematically evaluate the performance of the porous carbon-carbon nanotube composite material prepared in this invention as a silicon-carbon anode support, and to verify the key role of its three-dimensional conductive network and pore structure in nano-silicon deposition, volume expansion buffering, and improved cycle stability, we used the materials prepared in Examples 1-4 and Comparative Examples 1-5 as supports. We loaded nano-silicon using silane vapor deposition and then obtained silicon-carbon composite materials through acetylene carbon coating. These composite materials were then assembled into CR2032 coin-type lithium-ion half-cells for electrochemical performance testing. The specific steps are as follows:
[0119] (1) Silane deposition of loaded silicon: 0.3 g of carrier material was placed in a tube furnace and heated to 500 °C at 5 °C / min under an inert atmosphere (argon, flow rate 100 sccm). Silane gas (SiH4, flow rate 80 sccm) was introduced for vapor deposition for 2 h, so that nano-silicon was uniformly filled in the pores of porous carbon and the gaps in the carbon nanotube network.
[0120] (2) Carbon coating: After silicon deposition, the temperature is raised to 700℃ at 5℃ / min under an inert atmosphere, and acetylene gas (C2H2, flow rate 200 sccm) is introduced for carbon coating treatment for 2 h to form a protective carbon layer on the surface of silicon nanoparticles, thus obtaining silicon-carbon composite material.
[0121] (3) Assembly of lithium-ion button cells: The above-mentioned silicon-carbon composite material, sodium carboxymethyl cellulose (CMC) binder, styrene-butadiene rubber (SBR) binder, and conductive carbon black (Super P) are mixed in a mass ratio of 90:2:3:5. An appropriate amount of deionized water is added and stirred into a slurry. The slurry is coated onto a copper foil current collector with a thickness of 10 μm, and the coating thickness is about 100 μm. After vacuum drying at 100℃ for 12 h, it is cut into circular silicon-carbon negative electrode sheets with a diameter of 12 mm. The mass of the active material is accurately weighed and recorded. In an argon-filled glove box, the positive electrode shell, electrode sheet, Celgard 2500 separator (diameter 16 mm), 80 μL of 1 mol / L lithium hexafluorophosphate (LiPF6) ethylene carbonate / diethyl carbonate (EC / DEC, volume ratio 1:1) electrolyte, lithium sheet (diameter 14 mm, thickness 0.6 mm), gasket, spring sheet, and negative electrode shell are assembled into a 2032 type button lithium-ion half cell.
[0122] (4) Electrochemical testing: The assembled half-cell was placed at a constant temperature of 25℃ for 12 h before charge-discharge testing was performed. The voltage window was 0.01~2.0 V (vs. Li). + The samples (Li) were subjected to constant current charge-discharge tests at current densities of 0.1 A / g, 0.5 A / g, 1 A / g, 2 A / g, 5 A / g, and 10 A / g. Initial coulombic efficiency (ICE) = initial charge capacity / initial discharge capacity × 100%; rate performance was characterized by capacity retention at 10 A / g (relative to capacity at 0.1 A / g); cycle stability was tested at 1 A / g for 1000 charge-discharge cycles, and capacity retention (discharge capacity at 1000th cycle / discharge capacity at 1st cycle × 100%) was recorded. The electrochemical performance test results for each sample are summarized in Table 2.
[0123] Table 2 Comparison of electrochemical performance of silicon-carbon anodes for each sample
[0124]
[0125] As shown in Table 2, the carrier materials of each embodiment of the present invention exhibit excellent electrochemical performance in silicon-carbon anode applications. Among them, Example 1 shows the best overall performance, with a reversible capacity of 2029 mAh / g, a rate retention of 56% at 10 A / g, and a cycle retention of 88% after 1000 cycles. Examples 2-4 also show excellent performance, with reversible capacities of 1823-1956 mAh / g, rate retention of 47%-51%, and cycle retention of 81%-85%, indicating that the present invention has good universality for different carbon precursors and process routes.
[0126] Its performance advantage stems from the synergistic mechanism of "porous carbon with high specific surface area for silicon storage - three-dimensional conductive network of carbon nanotubes - confined pores buffering volume effect": the high specific surface area and well-developed pores of the porous carbon matrix provide sufficient deposition space and physical confinement sites for nano-silicon, effectively buffering the volume expansion during charge and discharge; the in-situ grown carbon nanotubes penetrate the carbon skeleton, constructing a continuous conductive network and enhancing the structural resistance to deformation, thereby significantly improving rate and cycle performance, which is significantly better than physically mixed carbon nanotubes (Comparative Example 2) and samples without CVD (Comparative Examples 1 and 5); the second stage of water vapor activation ensures the continuity of pores and ensures uniform deposition of silane. Omitting this step (Comparative Example 3) leads to a sharp decline in capacity and cycle performance. In comparison, Comparative Example 4 has a rate retention rate of only 12%, a cycle retention rate of 24%, and a capacity of only 674 mAh / g, which is far inferior to the embodiments of this invention.
[0127] In summary, the porous carbon / carbon nanotube composite material prepared by this invention, as a silicon-carbon anode carrier, significantly improves the capacity, rate performance, and cycle stability of the silicon-carbon anode through a multi-synergistic mechanism of "pore interconnection—confined silicon storage—conductive network—in-situ scaffold anti-deformation," demonstrating broad application prospects in the field of high-energy-density lithium-ion batteries.
Claims
1. A method for preparing a porous carbon nanotube composite material, characterized in that, Includes the following steps: (1) A porous carbon matrix loaded with transition metal nanoparticles is prepared, wherein the preparation is carried out by pre-doping or post-doping. The predoping method is as follows: after uniformly mixing the carbon-based precursor, activator and transition metal source, the mixture is subjected to high-temperature treatment under an inert atmosphere to simultaneously complete activation and pore formation, reduction of the transition metal source into metal elemental nanoparticles and catalytic graphitization. The post-doping method is as follows: first, the carbon-based precursor is mixed with an activator and activated at high temperature to form pores to obtain a porous carbon matrix; then, a transition metal source is loaded onto the porous carbon matrix and reduced at high temperature to obtain a porous carbon matrix loaded with metal elemental nanoparticles. (2) Using the metal nanoparticles obtained in step (1) as catalysts, carbon source gas is introduced under an inert atmosphere to carry out chemical vapor deposition reaction, and carbon nanotubes are grown in situ in the porous carbon framework. (3) Stop the introduction of carbon source gas, switch to an inert atmosphere, and carry out physical activation and / or chemical activation treatment; (4) After acid washing, water washing until neutral, and drying, a porous carbon nanotube composite material is obtained.
2. The preparation method according to claim 1, characterized in that, The activator is selected from any one or more chemical activators among KOH, NaOH, K2CO3, ZnCl2, and H3PO4, or from any one or more physical activating media among CO2 and water vapor; the mass ratio of the activator to the carbon-based precursor is (1:1) to (4:1).
3. The preparation method according to claim 1, characterized in that, The metal element in the transition metal source is selected from any one or more of Fe, Ni, Co, Cu, Mo, and Mn; the amount of transition metal source added is 0.5% to 15% of the mass of the metal element relative to the mass of the carbon-based precursor.
4. The preparation method according to claim 1, characterized in that, The carbon-based precursor is selected from any one or more of biomass, coal tar pitch, petroleum pitch, and resin.
5. The preparation method according to claim 1, characterized in that, In the pre-doping method, the high-temperature treatment is performed at a temperature of 700–1000℃ for 1–5 h; in the post-doping method, the high-temperature activation pore-forming temperature is 700–1000℃ for 1–5 h, and the high-temperature reduction temperature is 700–1000℃ for 0.5–2 h.
6. The preparation method according to claim 1, characterized in that, The carbon source gas in step (2) is selected from any one or more of methane, ethylene, acetylene, ethanol, and toluene; the temperature of the chemical vapor deposition reaction is 650-1100℃ and the reaction time is 20-300 min.
7. The preparation method according to claim 1, characterized in that, The physical activation medium in step (3) is selected from any one or more of water vapor and CO2, and the chemical activation agent is selected from any one or more of KOH, NaOH, and K2CO3; the temperature of the second stage of activation is 700-950℃ and the time is 20-120 min.
8. A porous carbon nanotube composite material, characterized in that, It is prepared by any one of claims 1 to 7.
9. The porous carbon nanotube composite material according to claim 8, characterized in that, The composite material comprises a porous carbon matrix, graphite microcrystals, and carbon nanotubes; the graphite microcrystals are uniformly distributed inside the porous carbon matrix, and the carbon nanotubes are intercalated and anchored in the framework of the porous carbon matrix; the graphite microcrystals and the carbon nanotubes synergistically construct a three-dimensional interconnected conductive network inside and on the surface of the porous carbon matrix; and there is an in-situ grown chemical / metallurgical bonding interface between the carbon nanotubes and the porous carbon matrix.
10. The application of the porous carbon nanotube composite material according to claim 8 in the silicon-carbon anode of supercapacitors or lithium-ion batteries.
Citation Information
Patent Citations
Porous carbon / carbon nanotube composite materials and their preparation methods, electrodes and supercapacitors
CN109786128B
A hard carbon composite negative electrode material and its preparation method and application
CN114447304B
